2018
DOI: 10.1038/s41565-018-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic coupling of site-controlled quantum emitters in monolayer WSe2 to plasmonic nanocavities

Abstract: Solid-state single-quantum emitters are a crucial resource for on-chip photonic quantum technologies and require efficient cavity-emitter coupling to realize quantum networks beyond the single-node level 1,2 . Previous approaches to enhance light-matter interactions rely on forming nanocavities around randomly located quantum dots 3-8 or color centers 9,10 but lack spatial control of the quantum emitter itself that is required for scaling. Here we demonstrate a deterministic approach to achieve Purcell-enhance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
299
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(316 citation statements)
references
References 36 publications
12
299
5
Order By: Relevance
“…The spatial modulation of the PL emission from InSe over the Si‐pillars is qualitatively different from that reported for single and bi‐layer TMDCs. [ 33–41 ] In TMDCs sharp emission lines are observed at low‐temperature and assigned to the recombination of excitons from localized states. These arise from crystal defects, non‐homogeneous strain and/or nano wrinkles intentionally created by exfoliating and/or transferring the TMDCs onto nanopillars, rough metallic surfaces coated with dielectrics, and/or created by intentionally structural damage of the layers.…”
Section: Resultsmentioning
confidence: 99%
“…The spatial modulation of the PL emission from InSe over the Si‐pillars is qualitatively different from that reported for single and bi‐layer TMDCs. [ 33–41 ] In TMDCs sharp emission lines are observed at low‐temperature and assigned to the recombination of excitons from localized states. These arise from crystal defects, non‐homogeneous strain and/or nano wrinkles intentionally created by exfoliating and/or transferring the TMDCs onto nanopillars, rough metallic surfaces coated with dielectrics, and/or created by intentionally structural damage of the layers.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that hBN grown via chemical vapor deposition (CVD) can contain a high density of point defects that can be "activated" (i.e., transformed into a fluorescent state) either by thermal annealing or substrate-engineering [33,34]. In this latter case, the emitter position (and, to some extent, the areal concentration [35]) can be controlled, hence providing opportunities for integration with photonic structures [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 However, the deterministic coupling of well-ordered quantum emitters in atomically thin materials with resonant plasmonic modes has only now been achieved. 33,36…”
Section: Introductionmentioning
confidence: 99%